The Sena Dynasty: From Bengal to Nepal - Das, Basudevlal (Academic Voices: A Multidisciplinary Journal, 2015)
The Sena dynasty ruled in Bengal up to 1205 AD. They were the patron of Hinduism. After the downfall of their rule in Bengal, their descendants proceeded towards westward. The neighboring area Mithila was also influenced by the Senas. So, a branch of the family proceeded towards this and established their settlement in the land of present day Nepal in about middle of the thirteenth century. The Senas appeared first in this land at Rupanagar, which is at present in Saptari district of Sagarmatha zone and afterwards they established Makawanpur kingdom, which is now a district of Narayani zone. From Makawanpur, they proceeded towards Palpa, Rajapur, Tanahu, Pyuthan, Risinga, Vinayakapur, Gulmi etc. The rule of the Senas ended in eithteenth century because of the new rising power of Gorkhalis. DOI: http://dx.doi.org/10.3126/av.v4i0.12350 Academic Voices Vol.4 2014: 9-16